2019
DOI: 10.1007/s10955-019-02451-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Condensed Phase in the Inclusion Process

Abstract: We establish a complete picture of condensation in the inclusion process in the thermodynamic limit with vanishing diffusion, covering all scaling regimes of the diffusion parameter and including large deviation results for the maximum occupation number. We make use of size-biased sampling to study the structure of the condensed phase, which can extend over more than one lattice site and exhibit an interesting hierarchical structure characterized by the Poisson-Dirichlet distribution. While this approach is es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Our goal here is to understand details of the condensed phase when it extends over more than one site and exhibits a non-trivial structure. Such structures have previously been observed as a result of spatial correlations [WE12, WSJMO09, TTCB10] and as a result of L-dependent stationary weights, with a soft cut-off for site occupation numbers under zero-range dynamics [SEM08] or in the inclusion process [JCG19].…”
Section: Introduction and Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Our goal here is to understand details of the condensed phase when it extends over more than one site and exhibits a non-trivial structure. Such structures have previously been observed as a result of spatial correlations [WE12, WSJMO09, TTCB10] and as a result of L-dependent stationary weights, with a soft cut-off for site occupation numbers under zero-range dynamics [SEM08] or in the inclusion process [JCG19].…”
Section: Introduction and Resultsmentioning
confidence: 63%
“…Our main result provides a generalization to models with more general weights that do not lead to exact expressions for Z L,N , and with non-trivial bulk distribution where 0 < ν ρ (η x ) < ρ. In our proof, we not only make use of the Poisson-Dirichlet distribution's characterisation via size-biased sampling, which was essential for the arguments in [JCG19], but also use the characterisation as the unique reversible distribution under split-merge dynamics as explained in Section 2.1. This allows us to avoid explicit expressions or approximations of the partition function Z L,N which are not always at hand.…”
Section: Introduction and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 6. 7 The choice of the space of all compactly supported smooth functions C := C ∞ k (R) as dense set for our Hilbert space turns out to be particularly convenient since it is a core of the Dirichlet form associated to the Brownian motion. As a consequence, we can make use of the same set also for proving that (41) is satisfied.…”
Section: Convergence Of Hilbert Spacesmentioning
confidence: 99%
“…In the context of the SIP on a finite lattice, the authors of [6] showed the emergence of condensates as the parameter k → 0, and rigorously characterize their dynamics. We also mention the recent work [7] where the structure of the condensed phase in SIP is analyzed in stationarity, in the thermodynamic limit. More recently in [8], condensation was proven for a large class of inclusion processes for which there is no explicit form of the invariant measures.…”
Section: Introductionmentioning
confidence: 99%